Frankfurt - Cassany, Mia (Tate Publishing, 2018)
"Pierre and Frankfurt have lived happily together in their top floor flat, since the first day they met! Frankfurt is the most refined little dog you could imagine. He drinks his tea without the slightest slurp, he never gobbles his food and arranges his toys and scarves according to size and colour. But there is one thing that really upsets Frankfurt - one word! His name! How could anyone ever take a sausage dog seriously with a name like that? But Frankfurt has a plan . . . Join Frankfurt and Pierre in this wonderful book picture book that celebrates the importance of identity and friendship."--Provided by publisher
Translation of: Frankfurt. - Originally published in Spanish: [Barcelona] : Mosquito Books Barcelona, SL, 2017
Keywords: Dachshunds / Juvenile fiction; Dogs / Juvenile fiction; Pets / Juvenile fiction; Names, Personal / Juvenile fiction; Pet owners / Juvenile fiction; Dachshunds; Dogs; Names, Personal; Pet owners; Pets; JUVENILE FICTION / Animals / Dogs; JUVENILE FICTION / Social Themes / Friendship; Name; Dackel; Unzufriedenheit; Tierhalter; Freundschaft; Bilderbuch